Not Everything Is Cordless Today—Case Report of Acute Intestinal Obstruction in a Neonate Due to Cord Clamping - Keese, Daniel; Schwalbach, Anne-Kathrin; Schmedding, Andrea; Rolle, Udo (Frontiers in Pediatrics, 2022)
We report a case of a 2-day-old neonate with bilious vomiting and abdominal distension. A small bowel obstruction with ileal perforation due to a misplaced clamping of the umbilical cord was apparent before laparotomy. This complication was a sequala after clamping the cord too close to the abdominal wall in a case where there was a hernia into the cord with intestinal content. A herniation of abdominal contents due to an omphalocele minor or a hernia must be taken into consideration during the inspection of the umbilical cord before clamping.